1909 N.M. Laws 333-34 - (:unkn) unknown (My University, 1909)
Ch. 117, § 8: That villages incorporated under this act shall have the power by ordinance, to prevent the presence within their limits of anything dangerous, offensive, unhealthy or indecent and to cause any nuisance to be abated; to regulate the transportation, storage and keeping of gun-powder and other combustibles and explosives, oils, gasoline and other articles which may endanger the property of such village[.]
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION